2001
DOI: 10.1099/0022-1317-50-5-430
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Helicobacter pylori infection by bovine milk glycoconjugates in a BALB/cA mouse model

Abstract: The attachment of Helicobacter pylori to the human gastric mucosa is a complex process involving several speci®c structures recognised by the cell surface receptors. Sialylated multivalent high mol. wt glycoproteins have been shown to inhibit H. pylori sialic acidspeci®c haemagglutination. This study explored whether sialylated glycoconjugates from bovine milk could inhibit an experimental H. pylori infection in a mouse model. BALB=cA mice (6±8 weeks old) were inoculated with a mouse-passaged H. pylori strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 15 publications
2
83
1
1
Order By: Relevance
“…For instance, lactotransferrin is only partly saturated with iron in its native state and can therefore have a bacteriostatic effect by competing with bacteria for iron (8). Lactotransferrin may also function as an antibiotic agent by virtue of its structural properties (13). The glycosylation of lactotransferrin has been characterized previously (14) and differs from that normally found in serum transferrin.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, lactotransferrin is only partly saturated with iron in its native state and can therefore have a bacteriostatic effect by competing with bacteria for iron (8). Lactotransferrin may also function as an antibiotic agent by virtue of its structural properties (13). The glycosylation of lactotransferrin has been characterized previously (14) and differs from that normally found in serum transferrin.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteriostatic activity of ALF is due in part to its iron chelating ability, which can deplete iron and restrict bacterial growth (48). ALF is also bactericidal against a wide range of bacteria, including Escherichia coli, Vibrio cholerae, Streptococcus mutans, and S. pneumoniae (4,24,58). The bactericidal activity of ALF is associated with the N-terminal 47 amino acids of the protein, which is part of the N-lobe (55).…”
mentioning
confidence: 99%
“…11 The administration of bLF to H. pylori-infected mice resulted in marked decrease of bacterial colonization, attachment, and inflammation irrespective of iron-free or partially iron-saturated preparations. 12,13 In humans with H. pylori infection, Di Mario et al showed that bLF combined in a triple eradication regimen (rabeprazole, clarithromycin, and tinidazole) significantly improved the eradication rate. 14 In the present study, we investigated the efficacy of a single administration of bLF in a randomized, double-blind, placebo-controlled trial.…”
Section: Introductionmentioning
confidence: 99%